Génesis de las costumbres no codificadas - Atefeh Roohi Kargar; Rasoul Parvin (Ius Humani. Jornal do direito, 2017)
The study of what is called “customary law” and “non-written rules” is always faced with ambiguity due to the lack of written resources. The reason for emphasizing the role of custom and applying the words on their customary meanings was to re-focus on this rich source of rights, which is far from sights. By reviewing the Articles, books and documentary data, we tried to look again at the status of unwritten conventions, legal rules and legal principles that could be interpreted as legal norms. If written or assigned to a bunch or a material to them, along with other laws they can be a good complement. This paper intends to review the role of custom and habit in concluding contracts by reviewing past comparative law studies and helping out the role of custom and unwritten rights. Besides, it intends to unify the material of Arts. 220, 225 and other Arts. of civil law of the parties to the awareness of the custom, because ignorance of the customary is not like ignorance of the law.